Orientation-Controlled Growth of Pt Films on SrTiO3 (001) by Atomic Layer Deposition - Pyeon, Jung Joon; Kang, Jun-Yun; Baek, Seung-Hyub; Kang, Chong-Yun; Kim, Jin-Sang; Jeong, Doo Seok; Kim, Seong Keun (AMER CHEMICAL SOC, 2015)
We grew Pt films on TiO2-terminated SrTiO3 (001) by atomic layer deposition, using trimethyl(methyl-cydopentadienyl)-platinum(IV) as the Pt source and O-2 and O-3 as the oxidants. The orientation of the Pt films grown with O-2 varied from (111) to (001) as the growth temperature was increased from 220 to 350 degrees C, while the Pt films grown with O-3 have a strong preference for the (111) orientation even at a high growth temperature of 350 degrees C. The difference in the orientation of the Pt films on SrTiO3 (001) was attributed to changes in the degree of chemical bonding across the Pt/SrTiO3 interface with respect to the oxidant. We observed an increase in Pt-O bonding at the interface between the Pt grown with O-3 and the SrTiO3 substrate. The interfacial energy of Pt (111)parallel to SrTiO3 (001) may have been significantly decreased by the increase in Pt-O bonding at the interface, which eventually led to the strong (111) preference of the Pt grown with O-3. The findings provide the possibility of controlling the orientation of Pt without manipulating the kinetic energy of crystal growth.
Keywords: THIN-FILMS; HYDROGEN-PRODUCTION; EPITAXIAL-GROWTH; PLATINUM; WATER